Personalizing Group Instruction Using Knowledge Space Theory and Clustering Techniques - Zakaria, Rim S. (2016)
A Master of Science thesis in Engineering Systems Management by Rim S. Zakaria entitled, "Personalizing Group Instruction Using Knowledge Space Theory and Clustering Techniques," submitted in May 2016. Thesis advisor is Dr. Imran A. Zualkernan. Soft and hard copy available.